Puedo, ou não posso: prós e contras do método cubano de alfabetização na América Latina e Brasil - Alvarenga, Marcus Vinícius de Mattos (2009)
This comparative study verifies the legitimating of statements that emerged in the Motion of Advertence from the VIII National Meeting of Adult Education, in which the Cuban method of literacy Yo, sí puedo had its appliance interdicted in Brazilian territory, with the arguments and claims that it is different from, or even against, the principles and the procedures of the Paulo Freire Method, that had created a legacy of emancipation in the country. Applying a comparative analysis of both methods propositions and using interviewing people involved with experiences with Yo, sí Puedo and Paulo Freire Method as well in the last years, within the country, one intends to deep the comparative analysis in order to ratify or to rectify convergences or divergences, approximations or distances, similitudes or differences.